Allyl trenbolone to control estrus in gilts -conception rate and litter size after treatment - Davis, Duane L.; Robl, J.M.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Control of estrus in gilts is theoretically possible by feeding a progestogen for 18 consecutive days. During the feeding period the progestogen suppresses estrus in all gilts and when withdrawn from the feed, all animals are expected to come in heat 4 to 7 days later. To be useful, the synchronizing agent must meet two criteria: (1) it must effectively control the time of estrus, and (2) it must not adversely affect fertility. We conducted this trial to evaluate a progestogen, allyl trenbolone, with respect to these criteria. Allyl trenbolone is not presently available to swine producers.
Keywords: Swine; Allyl trenbolone; Estrus; Gilts; Conception rate; Litter size